Nd-doped ZnO films on (100) MgO substrate: From metal to semiconductor. (1st November 2021) - Perrière, J.; Nistor, M.; Millon, E.; Cachoncinlle, C.; Hebert, C.; Jedrecy, N.
Abstract: We report a wide range of electric and magneto-transport properties of epitaxial Nd-doped ZnO thin films grown on (100) MgO single crystal substrate by pulsed-laser deposition under 10 −2 mbar high oxygen pressure as a function of the growth temperature Tg . The classical (001) texture of the ZnO wurtzite phase is present in all films whatever the growth temperature, while for Tg lower than 500 °C an additional epitaxial (100) texture is observed. These structural changes are accompanied by drastic modifications of the charge transport mechanisms. For Tg = 300 °C, the films behave as a metal from 300 to 275 K, from which temperature a metal-insulator transition occurs. The electrical behaviour between 275 and 50 K is described by the quantum correction to conductivity theory in disordered systems and comforted by magneto-resistance data. For Tg = 500 °C, a semiconducting behavior with partial metallic character is evidenced, while for Tg = 700 °C, pure semiconductor characteristics are obtained with variable-range hopping conductivity at low temperatures. Magneto-resistance measurements indicate that Nd 3+ ions act below 150 K as scattering centers for electrons only for films grown at 300 °C and 500 °C. These observations have to be related to the incorporation of Nd 3+ into the ZnO films during growth. The evolution from a metallic film to a semiconducting one, while acting on the single growth temperature parameter, opens new perspective in the context of charge transport.